Information Technology Adoption, Corporate Governance and Bank Performance - Umi Muawanah; Gunadi Gunadi (Universitas Airlangga, 2018)
Many academicians and practitioners have been acknowledging that information technology (IT) adoption could improve company performance. However, previous research indicates contradictory evidence. These inconsistencies can be attributed to variations among the studies in choosing proxy for IT adoption and due to contingent on other factors. This research aims at analyzing the influence of a contingent factor that is corporate governance (CG) concerning the effectiveness of IT adoption in influencing company performance measured by change in return on assets. Two proxies are used for IT adoption: company expenses on IT and the level of the organization managing IT. Data is collected and analyzed from annual reports of all banks listed in Indonesia Stock Exchange from 2011 to 2013. Multiple linear regression models are employed. This research shows that corporate governance practice could improve the effectiveness of IT adoption in improving company performance. This research implies that better CG practices in providing direction and monitoring on IT can lead to better company performance.